2010
DOI: 10.1007/s00253-010-2583-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing antibiotic resistance burden in municipal wastewater treatment plants

Abstract: Municipal wastewater treatment plants are recognized reservoirs of antibiotic-resistant bacteria. Three municipal wastewater treatment plants differing on the dimensions and bio-treatment processes were compared for the loads of amoxicillin-, tetracycline-, and ciprofloxacin-resistant heterotrophic bacteria, enterobacteria, and enterococci in the raw inflow and in the treated effluents. The sewage received by each plant, in average, corresponded to 85,000 inhabitant equivalents (IE), including pretreated indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 162 publications
(98 citation statements)
references
References 21 publications
8
83
1
1
Order By: Relevance
“…E. coli isolates with MDR phenotype were detected in all samples, comprising from 6 % (in VR and DMOut) to 13 % (in WMOut) of isolates. The positive selection of bacteria with resistance patterns, previously described in wastewater processes (Łuczkiewicz et al 2010;Ferreira da Silva et al 2007;Novo and Manaia 2010), was also observed in this study for both of the WWTPs. Resistance rate to AMC, STX, CIP, and LVX noted for E. coli isolated from treated wastewater (WTW and DTW) was higher than that observed in corresponding raw wastewater (WRW and DRW), but the differences were not statistically significant (in Fisher's exact test).…”
Section: E Coli With Antibiotic and Multiple-antibiotic Resistancesupporting
confidence: 51%
“…E. coli isolates with MDR phenotype were detected in all samples, comprising from 6 % (in VR and DMOut) to 13 % (in WMOut) of isolates. The positive selection of bacteria with resistance patterns, previously described in wastewater processes (Łuczkiewicz et al 2010;Ferreira da Silva et al 2007;Novo and Manaia 2010), was also observed in this study for both of the WWTPs. Resistance rate to AMC, STX, CIP, and LVX noted for E. coli isolated from treated wastewater (WTW and DTW) was higher than that observed in corresponding raw wastewater (WRW and DRW), but the differences were not statistically significant (in Fisher's exact test).…”
Section: E Coli With Antibiotic and Multiple-antibiotic Resistancesupporting
confidence: 51%
“…The observed bacterial elimination (2 log) after passage through the WWTP is typical of activated sludge processes (Łuczkiewicz et al, 2010;Novo and Manaia, 2010). Although more than 90% of integrons were eliminated, the normalized copy number of class 1 and class 2 integrons was not reduced, and around 10 16 integrons were released each day into environmental water ( Figure 5).…”
Section: Hospital Effluent Impact On Integron Dissemination T Staldermentioning
confidence: 92%
“…The first involves the isolation of bacteria and antibiotic susceptibility testing, using methods and classification criteria originally proposed for clinical bacteria (e.g., European Committee on Antimicrobial Susceptibility Testing, EUCAST or the Clinical and Laboratory Standards Institute, CLSI). The selection of bacteria tolerant to antibiotics supplemented in the culture media has also been used (Watkinson et al 2007;Novo and Manaia 2010;Manaia et al 2011;Novo et al 2013). These methods have provided a good overview of the resistance occurrence in some bacterial groups of human-commensal and environmental bacteria.…”
Section: Methods Harmonization and Data Sharingmentioning
confidence: 99%
“…Several studies have demonstrated that wastewater treatment using different technologies and complying with the established recommendations regarding treatment efficiency removes, in general, ARB at the same rate as the total bacteria Rizzo et al 2013b;Vaz-Moreira et al 2014). In a study comparing different conventional treatment systems-activated sludge, trickling filter, and submerged aerated filter-it was concluded that the most important factor on antibiotic resistance removal was the capacity of the treatment to remove bacteria, while longer retention times, as those used in la-goons, could be considered a factor favoring antibiotic resistance proliferation Novo and Manaia 2010). In other studies, it was shown that some resistance types, such as quinolone resistance in coliforms or enterococci, tend to become more prevalent in the final effluent, after activated sludge treatment, than in the raw wastewater and this effect could be noticed mainly in the winter (Ferreira da Silva et al 2006;Łuczkiewicz et al 2010;Novo et al 2013).…”
Section: Urban Wastewater Treatmentmentioning
confidence: 99%